A study on the customer perception towards service quality at Business Management Department Majlis Bandaraya Alor Star / Noorashikin Harun @ Che Ani - Harun @ Che Ani, Noorashikin (Faculty of Business and Management, UiTM Perlis, 2005)
Service is an identifiable, intangible activity that is the main objective of transaction that serve to meet the needs of customers. Service quality is the ability of the organization to meet or exceed customer expectations. Research into what represents quality in service delivery has demonstrates the significance of the customer in any measurement undertaken. Customer perspectives on what represents quality may vary over time and between customers. Involvement by those providing a service in quality development is identified as important due to the significance of the customer and customer satisfaction in how quality of a service is viewed. It is seen that such knowledge at a service delivery level can influence management decisions. Furthermore, the purpose of this study is to determine the level of Customer Perception Towards Service Quality offered by Business Management Department, at Majlis Bandaraya Alor Star. Good service quality exists when customer expectation are met or exceeded and is studied in five dimensions “reliability, empathy, assurance, responsiveness and tangibility (Parasuraman, Zeithaml and Berry , 1985). The idea of this research is to observe and at the same time lead to some recommendation to cope with existing problem. In order to address this issues, 100 questionnaires were distributed to the Business Management Department customers. The sample are selected by using simple random sampling technique to consider all the element in the population and each element has an equal chance of being chosen as the subject. The findings and hypothesis are going to be analyzed by using Statistical Program For Social Science (SPSS) software in order to get the best statistical techniques in interpreting the results.